AKIBAT HUKUM PENGGUNA JASA PROSTITUSI ONLINE DENGAN MELIBATKAN ANAK DIBAWAH UMUR - Feby Mulyanita; Nynda Fatmawati Octarina (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
Along with the development of technology and information, making it easier for the community. The impact obtained from this convenience, of course, is not only the positive impact, but also the negative impact, one of which is the growing crime of prostitution carried out online. In its activities it would be a problem if it involved minors as the subject, whether it be pimps, waiters, or users. Users who are minors are motivated to try new things considering they are still in the search for self-patterns. The aim of this research is to find out the legal consequences of users of online prostitution services who are minors. In this study, normative research methods will be used to examine and approach legislation as material in analyzing and discussing it. The conclusion states that if a child is in conflict with the law related to online prostitution, he can be punished as a last resort with a penalty of half of the maximum penalty of 15 years in prison and a maximum fine of 5 billion rupiah.